Hepatitis C infection among drug users in northern Thailand - Jaroon Jittiwutikarn (2018)
Illicit drug users are commonly infected with hepatitis C virus (HCV) and human immunodeficiency virus (HIV). We evaluated the prevalence, incidence, and risk behaviors associated with HCV infection in 1,859 drug users in northern Thailand. The HCV prevalence was 27.3%: 86.0% among drug injectors (IDUs) and 5.3% among those who did not inject. Sexual behavior was not significantly associated with HCV among IDUs or drug users who used but didn't inject illicit drugs; only injection behaviors were independently associated with HCV in multivariate analysis. Among men, a history and increasing frequency of injecting drugs, older age, and a history of incarceration were associated with HCV infection. Among 514 opiate users who were HCV and HIV seronegative at baseline, 41 incident HCV infections and 6 HIV infections occurred on follow-up; the HCV incidence was 5.43/100 person-years; it was 44.3/100 person-years in IDUs and 1.9/100 person-years in non-injectors. HCV and HIV among drug users in Thailand are common and primarily associated with injection behavior. Copyright © 2006 by The American Society of Tropical Medicine and Hygiene.